1
$\begingroup$

$$P_x=\lim_{M\rightarrow \infty }\frac{1}{2M+1}\sum_{n=-M}^{M}\left | x[n] \right |^2$$

I have used this formula to find out the powers for different signals, but the sum part of the formula still puzzles me. Lets take one example: $$x[n] = 4i+1$$ Simply calculating the absolute value, I got this: $$|x[n]|^2=|4i+1|^2=(\sqrt{4^2+1^2})^2=17$$ 17 seems to be the answer I got after going through the rest of the formula, but I am not sure how the sum works. By using Wolframa, I arrived at: $$\sum_{n=-M}^{M}17 =34M+17$$ Which would complete the limit part of the formula with the final result of 17, as discussed. How does this sum function, as described above?

$\endgroup$
4
  • $\begingroup$ I don't really understand. If $x[4]$ only equal to $4i+1$, or all the signal values? $\endgroup$ Commented Nov 4, 2019 at 19:53
  • $\begingroup$ For any constant $c$, $M\ge 0$, $\sum_{-M}^{M} c = (2M+1)c$ $\endgroup$ Commented Nov 4, 2019 at 19:54
  • 2
    $\begingroup$ how does this sum function ? What do you mean by this phrase ? $\endgroup$
    – Fat32
    Commented Nov 4, 2019 at 20:37
  • $\begingroup$ @LaurentDuval That makes sense, but how can I derive that formula for $$(2M+1)c$$? The x[4] part was a mistake, corrected it. $\endgroup$ Commented Nov 4, 2019 at 21:14

2 Answers 2

1
$\begingroup$

A more general expression states that for $ M \geq N$:

$$ \sum_{n= N}^{n = M} c = (M-N+1) \cdot c $$

where the derivation simply relies on fact that the epxression has (M-N+1) terms :

$$ \sum_{n= N}^{n = M} c = \{ c + c + ... + c\} = (M-N+1) \cdot c $$

And when applied for your particular case (with $N = -M$) it becomes: $$ \sum_{n= -M}^{n = M} c = (M-(-M)+1) \cdot c = (2M+1) \cdot c $$

$\endgroup$
0
$\begingroup$

For instance, from $-3$ to $3$, you have $-3,\,-2\,-1,\,0\,1,\,2,\,3$, hence $2\times 3+1$ terms. More generally, the sum from $-M$ to $M$ is composed of $2M+1$ terms:

  • indices with $m$ strictly negative (a total of $M$),
  • those which $m$ strictly positive (a total of $M$),
  • plus one at zero ($1$).

If all terms are the same constant $c$, the total is $(2M+1)c$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.